Area- and Individual-Level Correlates of Self-Rated Health: Implications for Geographic Health Disparities - Jennifer L. Moss; Siddhartha Roy; Karl T. Clebak; Julie Radico; Jarrett Sell; Christina Scartozzi; Shuai Zhou; Guangqing Chi; Tamara Oser (SAGE Publishing, 2021)
Background Self-rated health (SRH) is a common measure of overall health. However, little is known about multilevel correlates of physical and mental SRH. Methods Patients attending primary care clinics completed a survey before their appointment, which we linked to community data from American Community Survey and other sources (n = 455). We conducted multilevel logistic regression to assess correlates of excellent/very good versus good/fair/poor physical and mental SRH. Results 43.9% of participants had excellent/very good physical SRH, and 55.2% had excellent/very good mental SRH. Physical SRH was associated with age (odds ratio[OR] = 0.82 per 10 years; 95% confidence interval[CI] = 0.72-0.93) and community correlates, including retail establishment density (OR = 0.94, 95% CI = 0.90-0.99) and percent of students eligible for free/reduced lunch (OR = 1.60, 95% CI = 1.08-2.38) (all P  < .05). Mental SRH was not associated with any characteristics. Conclusions Practitioners in public health, social work, and medicine could use zip codes to intervene in patients and communities to improve physical SRH.